Objective Assessment of Nasal Patency - Giotakis, Aristeidis I.; Tomazic, Peter Valentin; Riechelmann, Herbert; Vent, Julia (Facial Plastic Surgery, 2017)
The aim to objectify nasal airflow and patency is ongoing—many methods have been suggested, often lacking clinical relevance or showing weak correlations with patients' symptoms. It is crucial to thoroughly consult our patients presenting with nasal obstruction—and to inform them about realistic possible surgical outcomes. Often, a perfect-looking internal nose with a straight septum and normal-appearing turbinates does not guarantee a happy, symptom-free “owner.” A review of the literature and the current technical market is presented here to facilitate the rhinosurgeon's decision to perform pre- and postoperative objective measurements of nasal airflow. Recommendations by the societies have been included.
Keywords: assessment of nasal airflow; nasal function; obstruction; nasal ventilation; breathing